Automated and high accuracy out-of-hospital heart diseases early detection system - Hussein, Ahmed Faeq; Hashim, Shaiful Jahari; Abdul Aziz, Ahamd Fazli; Rokhani, Fakhrul Zaman; Wan Adnan, Wan Azizun (Elsevier, 2017)
Background: ECG measurement and analysis being performed in-hospital normally check patients with obvious symptoms. Asymptomatic patients, for example, those with silent ischemia, paroxysmal atrial fibrillation and Brugada syndrome are very difficult to detect using in-hospital ECG system. To make matter worst, conventional ECG analysis techniques only focuses in time domain that limits the sensitivity, specificity and accuracy of the interpretation due to ECG signals non-stationary nature. Most recent researches have proposed linear joint time-frequency analysis to overcome these limitations, however, their linear methods limit their accuracy.